A review on the recovery and separation of rare earths and transition metals from secondary resources. (20th May 2019) - Swain, Nilam; Mishra, Sujata
Abstract: The continuous miniaturization of modern green and advanced technologies is increasing the demand of rare earth elements (REEs). Consequently, REEs are listed as the critical metals concerning their crucial role for a clean environment. However, their resources are limited which in turn disrupt their supply chain. To tackle the supply issue and to meet future demand, there is need to exploit recycling schemes for the recovery REEs from secondary resources. This review describes comprehensively various processes developed for the separation of REEs and transition metals from secondary resources. It focuses on the hydrometallurgical route, especially solvent extraction employed to separate REEs and transition metals from potential wastes originated from different industries. The use of different commercial extractants for the recycling purposes and mechanisms involved in the extraction has been discussed in detail. Graphical abstract: Image 1009 Highlights: REEs are listed as the critical metals concerning their crucial role for a clean environment. The exploitation of recycling schemes for recovery REEs from secondary resources is important. Various processes developed for separating REEs and transition metals from secondary resources. Solvent extraction technique proves beneficial in the separation of REEs and transition metals.